The military as a separate society consequences for discipline in the United States and Australia - Collins, Pauline (Lexington Books, 2019)
Using the United States and Australia as examples, Collins argues that the justification for separateness weakens both the military standing and the practice of civilian control of the military on top of leading to an overall decline in morality and values in a democratic society
Keywords: Australien -- Army; USA -- Army; Disziplin; Moralisches Handeln; Militär; USA; Australien; Electronic books; Civil-military relations; Military discipline / Australia; Military discipline / United States; Power (Social sciences); Moral conditions; Sociology, Military; Military discipline; Australia; United States